Democratic Versus Socialist Multicultural Federalism: The Dilemma of Ethiopian Federalism. Issue 4 (December 2022) - Tareke, Sibuh Gebeyaw
The Ethiopian Constitution currently in use was introduced in 1995. It has facilitated the country's transformation from the Derg military regime to a decentralized democratic federal state that accommodates multi-ethnic diversity and institutionalizes ethnic identity. However, the de facto ethnic federal system is a mixture of socialist and democratic federalism. This federal experiment has faced enormous challenges, including problems of legitimacy, weak democratization, political instability, secession, and violent conflict between different ethnic groups. These problems have led to the internal displacement of people and the death of a large number of innocent citizens. This article assesses the prevailing mixture of democratic and socialist federalism in the context of the contemporary Ethiopian political milieu, particularly the challenges and impacts.